2017
DOI: 10.1016/j.bbrc.2017.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Snail transcription factor NLS and importin β1 regulate the subcellular localization of Cathepsin L and Cux1

Abstract: Several recent studies have highlighted an additional unexpected localization and site of action for Cathepsin L (Cat L) protease within the nucleus in breast, colon and prostate cancer, however, its role in the nucleus was unclear. It was proposed to mediate proteolytic processing of the transcription factor CCAAT-displacement protein/cut homeobox transcription factor (Cux1) from the full-length p200 isoform to generate the p110 and p90 isoforms, of which the p110 isoform was shown to act as a cell cycle regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…However, inhibition of both lysosomal and extracellular cathepsin L are not likely to cause a decrease in the expression of M2 markers. A lesser known function of cathepsin L is its role in regulating the transcriptional activator, CCAAT-displacement protein/cut homeobox (CDP/Cux) in the nucleus [39, 40]. Nuclear cathepsin L cleaves Cux, resulting in the activation of the Cux transcription factor [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibition of both lysosomal and extracellular cathepsin L are not likely to cause a decrease in the expression of M2 markers. A lesser known function of cathepsin L is its role in regulating the transcriptional activator, CCAAT-displacement protein/cut homeobox (CDP/Cux) in the nucleus [39, 40]. Nuclear cathepsin L cleaves Cux, resulting in the activation of the Cux transcription factor [39].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of HSP90-Cathepsin D cleavage-null mutants, partially prevented apoptosis of U937 and Jurkat cells highlighting a central role for Cathepsin D in HSP90 level regulation in LL, LMP and apoptosis. Meanwhile, Burton et al (2017) linked nuclear Cathepsin L with CUX1 proteolytic processing and thus linked Cathepsin L with EMT (and MET) progression in BC and PC cells [142]. Interestingly, in this study subcellular Cathepsin L was also observed to translocate from the nucleus to the cytoplasm, highlighting a novel protein trafficking-function for Cathepsin L. Kim et al (2018) showed that Cathepsin S could bind BRCA1 and facilitate it's ubiquitination and breakdown, thus suppressing DNA repair in BC development, while knocked-down expression of Cathepsin S stabilized BRCA1 levels, thus collectively linking Cathepsin S to BRCA1 signaling transduction [143].…”
Section: Signal Transduction Intermediates and Cathepsin Regulationmentioning
confidence: 99%
“…The classical importin-dependent mechanism for nuclear transport is well known for importin α/β/NLScargo complex, of which importin α discriminates the NLS, and importin β executes the association with small regulatory Ran-GTP to ship the complex into the nucleus [5,22,[50][51][52]. Moreover, proteins imported into the nucleus also can directly attach to importin β beyond the engagement of importin α-like adaptor [53]. Up to now, some herpesvirus-encoded proteins are reported to be transported into the nucleus by diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%